Decoding G-Quadruplexes Sequence in Vitis vinifera: Regulatory Region Enrichment, Drought Stress Adaptation, and Sugar–Acid Metabolism Modulation - Jun Xie; Kangkang Song; Gaixia Qiao; Rong Wang; Hongyuan Wu; Qiaoxia Jia; Yujuan Liu; Yi Li; Meilong Xu (Plants)
G-quadruplexes play a crucial role in transcription, translation, and DNA replication in plant genomes. Here, we comprehensively examined the prevalence and functions of G-quadruplexes in Vitis vinifera. A total of 467,813 G-quadruplexes were identified in grapevine genome, with enrichment in the promoter (0.54/kbp) and near transcription start sites (TSSs, 1.00/kbp), and showed conservative strand preference. The G-quadruplex density in centromeres exhibited heterogeneity. The differentially expressed genes (DEGs) under two-day drought stress manifested high G-quadruplex density in the promoter and TSS regions. The upregulated DEGs showed template strand-biased G-quadruplex enrichment, while downregulated DEGs displayed coding strand dominance linked to metal ion homeostasis and sugar–acid metabolism pathways, respectively. G-quadruplexes were enriched in key sugar–acid metabolism genes, including pyruvate kinase and sucrose synthase. The number of G-quadruplexes in sucrose transferase VINV genes was higher than that in the CWINV and NINV genes. This study revealed G-quadruplexes as regulatory elements of stress response and berry development, providing abundant genetic targets for precision breeding and the quality improvement of grapevines.